Larvicidal activity of peltopholum pterocarpum extract against aedes aegypti, culex quinquefasciatus and anopheles dirus - Natharinee Horata (2015)
Joint International Tropical Medicine Meeting 2013: Towards global health: an Asian paradigm of Tropical Medicine 11-13 December 2013 Centara Grand Bangkok Convention Center at Central World, Bangkok, Thailand. Bangkok: Faculty of Tropical Medicine, Mahidol University; 2013. p.148.